Cholinergic modulation of the medial prefrontal cortex: the role of nicotinic receptors in attention and regulation of neuronal activity - Bloem, Bernard; Poorthuis, Rogier B.; Mansvelder, Huibert D. (Frontiers in Neural Circuits, 2014)
Acetylcholine release in the medial prefrontal cortex is (mPFC) crucial for normal cognitive performance. Despite the fact that many have studied how acetylcholine affects neuronal processing in the mPFC and thereby influences attention behavior, there is still a lot unknown about how this occurs. Here we will review the evidence that cholinergic modulation of the mPFC plays a role in attention and we will summarize the current knowledge about the role between acetylcholine receptors and behavior and how acetylcholine receptor activation changes processing in the cortical microcircuitry. Recent evidence implicates fast phasic release of acetylcholine in cue detection and attention. This review will focus mainly on the fast ionotropic nicotinic receptors and less on the metabotropic muscarinic receptors. Finally, we will review limitations of the existing studies and address how innovative technologies might push the field forward in order to gain understanding into the relation between acetylcholine, neuronal activity and behavior.